Probing Anticancer Molecules from Onion Peels Waste; First Synthesis and Biological Studies of a Rare Quercetin Derivative-pachypodol - Nanjan, Pandurangan; Nambiar, Jyotsna; Bose, Chinchu; Banerji, Asoke; Nair, Bipin G. (Current Bioactive Compounds, 2025)
BackgroundThe constant increase in global onion production escalates the generation of onion peel waste. For instance, globally, >50 lakh tons of onion waste are generated annually.MethodsIts objectionable odor precludes its use in agriculture or disposal as landfilling presents environmental issues. Previous studies show that two major flavonoids, quercetin and its glycosides (spiraeoside), have been identified in abundance in onion waste. By utilizing the spiraeoside (quercetin-4ʹ-glucoside), a rapid synthesis of pachypodol (quercetin-3,3′,7-trimethyl ether, and a rare flavonol), an essential Ayurvedic product, has been developed and achieved. Pachypodol and analogs were studied for their ability to inhibit matrix metalloproteinase-2 and -9 (MMP-2 & 9) activity. Amongst the compounds tested, pachypodol significantly inhibited MMP-2 activity.ResultsIn-silico docking studies suggest that, unlike most known MMP inhibitors, pachypodol interacts selectively with MMP-2 through the residues Ile222, Tyr223, and Thr227 in a zinc-independent manner.ConclusionThe experimental studies also prove that pachypodol inhibits the MMP-2 enzyme in a zinc-independent way.
Keywords: enzyme